(-3)*(-3)*(-3)+x=10x

Simple and best practice solution for (-3)*(-3)*(-3)+x=10x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-3)*(-3)*(-3)+x=10x equation:


Simplifying
(-3)(-3)(-3) + x = 10x

Multiply -3 * -3
9 * -3 + x = 10x

Multiply 9 * -3
-27 + x = 10x

Solving
-27 + x = 10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10x' to each side of the equation.
-27 + x + -10x = 10x + -10x

Combine like terms: x + -10x = -9x
-27 + -9x = 10x + -10x

Combine like terms: 10x + -10x = 0
-27 + -9x = 0

Add '27' to each side of the equation.
-27 + 27 + -9x = 0 + 27

Combine like terms: -27 + 27 = 0
0 + -9x = 0 + 27
-9x = 0 + 27

Combine like terms: 0 + 27 = 27
-9x = 27

Divide each side by '-9'.
x = -3

Simplifying
x = -3

See similar equations:

| p/4-1=3 | | 4.7x+3.8=13.2l | | -2v+5v=-12 | | 445.53=.71x | | d/3-6=-2 | | X/8=21/14 | | x/4-9=-11 | | 5n-5=5n+10 | | 2/5*25=10 | | 4x+6y=4200 | | -11x=17 | | 2x-66=12 | | 7d+3=94 | | -9=-2v+5 | | 1/3xyz=p | | h/4-6=-1 | | 22-5p=57 | | q/8-1=2 | | 8x+4=92 | | 4x-6-2x=4 | | Q-1/21/2 | | -5+2m=25 | | 5=n/2-5 | | 6+6d=54 | | 8x-9=143 | | z/3-1=1 | | 5x-4+6x-9-4=2+2x+7 | | -2+10n=78 | | 2x+3-7(x-1)=2(x-55)+5x | | 1/7f-5(1/5)=9/14 | | a/6-1=2 | | p/9=93=-84 |

Equations solver categories